Enhanced membrane protein production in HEK293T cells via ATF4 gene knockout: A CRISPR-Cas9 mediated approach - Byung-Jo Choi; Ba Reum Kim; Ho Joong Choi; Ok-Hee Kim; Say-June Kim (Biomolecules & Biomedicine)
HEK293T cells are extensively utilized for therapeutic protein production due to their human origin, which enables accurate post-translational modifications. This study aimed to enhance membrane protein production in HEK293T cells by knocking out the ATF4 gene using CRISPR-Cas9 technology. The ATF4 gene was edited by infecting HEK293T cells with a lentivirus carrying optimized single-guide RNA (ATF4-KO-3) and Cas9 genes. Comparative evaluations were conducted using all-in-one and two-vector systems. Genome sequencing and membrane protein productivity of ATF4-KO cells were compared to wild-type cells using next-generation sequencing (NGS) and a membrane protein isolation kit, respectively. Single-cell analysis confirmed gene editing patterns, with NGS verifying the intended deletions. Membrane protein production was also assessed indirectly via flow cytometry, analyzing cells expressing Membrane-GFP. Compared to wild-type cells, ATF4-KO cells exhibited a significant increase in membrane protein production, with a 52.2 ± 19.0% improvement. Gene editing efficiency was compared between the two delivery systems, with the two-vector system demonstrating higher efficiency based on T7E1 assays. Western blot analysis confirmed ATF4 suppression and increased expression of membrane proteins, including E-cadherin and CD63. Quantitative analysis via PAGE revealed a 77.2 ± 30.6% increase in purified membrane protein yields, consistent with the observed enhancements. Flow cytometry using Membrane-GFP further demonstrated a 22.9 ± 9.7% increase in productivity. In summary, ATF4 knockout significantly enhances membrane protein production in HEK293T cells, offering potential improvements in biopharmaceutical manufacturing by enabling more efficient protein synthesis.